MODELED HYDROLOGIC RESPONSE UNDER CLIMATE CHANGE IMPACTS OVER THE BANKHEAD NATIONAL FOREST IN NORTHERN ALABAMA - Acharya, Anil (European Scientific Journal, ESJ, 2015)
The impacts of climate change on water availability over the Bankhead National Forest (BNF) and Sipsey Fork Watershed (SFW) located in northern Alabama is evaluated by developing a site specific hydrologic model inside the Soil and Water Assessment Tool (SWAT). The SWAT model is utilized over Sipsey Fork (SF) subbasin of SFW to assess hydrological response under changing climatic conditions until 2100. Calibration and validation of the SWAT model is performed at daily time steps by comparing simulated and observed streamflow. Altogether 13 parameters that directly influence surface/base flow and basin response were selected and calibrated; the model simulated streamflow very well as evidenced by correlation and error statistics (“r = 0.87“, “R2 = 0.75“, and lower “RMSE = 12 cms“). Climate forcing (e.g. precipitation, temperature) from selected regional/global climate models that represent regional climatology well over the basin were incorporated into the SWAT model to determine future water availability in the basin. The projected average change in total annual streamflow for SF varies from -10% to -18%, which ranges -7% to -16% for A1B, and -12% to -23% for A2 until 2100. This study is conducted in conjunction with other ongoing studies that looked at the impacts of forest management on BNF hydrology. Major research findings from this study will help decision makers in evaluating the combined impacts of climate change and forest management on water availability, and developing strategies to sustain available natural resources.